ОПТИМІЗАЦІЯ ДОБОВОГО ГРАФІКУ РОБОТИ ГІДРОЕЛЕКТРОСТАНЦІЇ З УРАХУВАННЯМ НЕЛІНІЙНОЇ ФУНКЦІЇ ВИТРАТ НА ВЛАСНІ ПОТРЕБИ - Олефір, Д.О.; Парус, Є.В.; Рибіна, О.Б.; Мірошник, В.О. (Інститут електродинаміки Національної академії наук України, 2024)
A mathematical model of the daily distribution of the available hydro resources of the dam hydroelectric power station is presented, taking into account the non-linear function of technological costs of electrical energy. The profit function from the sale of electric energy in the Day-ahead market is given. A linear and non-linear function of costs for the purchase of electric energy to cover the own power consumption needs of HPP generators under different modes of their loading is presented. The objective function of the profit from the sale of electricity on the day-ahead market is presented, taking into account the cost of purchasing electricity to cover the technological needs of the operation of hydropower generators in different loading modes. The system of limitations of hydro resources in the technological node "Reservoir - HPP" is given. Test calculations were performed using the presented mathematical models and the results of such calculations were analyzed. Ref. 8, fig. 3.